2021
DOI: 10.24998/maeusabed.996891
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Some Ecute Phase Proteins, Cytokines and Hepcidin Levels in Naturally Infected Saanen Goats with Paratuberculosis

Abstract: Johne's Disease or paratuberculosis is a mycobacterial infection of ruminants and has a global economical impact. Mycobacterium avium subsp. paratuberculosis is the cause of this disease. It reduces milk production, cause chronic weight loss leading death and major losses. Acute phase reactions are defined as minimum 25% increase or decrease in serum concentrations of acute phase proteins which are triggered by pro or antiinflammatory cytokines released from various cells or tissues. The aim of the study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Showing a faster response to an experimental inflammatory stimulus than other APPs in goats, SAA can be a major APP (increase up to 22 folds) indicating an acute condition (González et al, 2008). In a study on goats naturally infected with paratuberculosis, SAA concentration was reported to increase (Sevgisunar and Şahinduran, 2021). Demirbas and Kabu (2021) determined in their study on pneumonic goats that SAA concentration was higher in the pneumonic group than the healthy goats.…”
Section: Resultsmentioning
confidence: 98%
“…Showing a faster response to an experimental inflammatory stimulus than other APPs in goats, SAA can be a major APP (increase up to 22 folds) indicating an acute condition (González et al, 2008). In a study on goats naturally infected with paratuberculosis, SAA concentration was reported to increase (Sevgisunar and Şahinduran, 2021). Demirbas and Kabu (2021) determined in their study on pneumonic goats that SAA concentration was higher in the pneumonic group than the healthy goats.…”
Section: Resultsmentioning
confidence: 98%
“…The haemogram (for whole blood analysis) from samples was obtained before necropsy in the sodium EDTA-containing tubes. The procedure was then carried out utilising a Diatron (Budapest, Hungary) Abacus Junior vet haematology analyser device (Sevgisunar, 2017).…”
Section: Animal Experimental Designmentioning
confidence: 99%
“…Hepcidin (HEPC) is also classified as an AMP, namely defensin, with multiple immune activities despite having four cysteine (disulfide) bridges instead of three (as in classical defensins). The main site of HEPC production is the liver, but it is also detected in the kidneys, pancreatic beta cells, adipose tissue, heart, and body fluids [14]. It has direct antiviral and antimicrobial activity, but HEPC also takes part in iron metabolism.…”
Section: Introductionmentioning
confidence: 99%